Codon usage provide insights into the adaptation of rice genes under stress condition - Tyagi, Swati; Kabade, Pramod Gorakhanath; Gnanapragasam, Niranjani; Singh, Uma Maheshwar; Gurjar, Anoop Kishor Singh; Rai, Ashutosh; Sinha, Pallavi; Kumar, Arvind; Singh, Vikas Kumar (MDPI, 2023)
Plants experience different stresses, i.e., abiotic, or biotic, and to combat them, plants re-program the expression of growth-, metabolism-, and resistance-related genes. These genes differ in their synonymous codon usage frequency and show codon usage bias. Here, we investigated the correlation among codon usage bias, gene expression, and underlying mechanisms in rice under abiotic and biotic stress conditions. The results indicated that genes with higher expression (up- or downregulated) levels had high GC content (≥60%), a low effective number of codon usage (≤40), and exhibited strong biases towards the codons with C/G at the third nucleotide position, irrespective of stress received. TTC, ATC, and CTC were the most preferred codons, while TAC, CAC, AAC, GAC, and TGC were moderately preferred under any stress (abiotic or biotic) condition. Additionally, downregulated genes are under mutational pressure (R2 ≥ 0.5) while upregulated genes are under natural selection pressure (R2 ≤ 0.5). Based on these results, we also identified the possible target codons that can be used to design an optimized set of genes with specific codons to develop climate-resilient varieties. Conclusively, under stress, rice has a bias towards codon usage which is correlated with GC content, gene expression level, and gene length.